Sistem Monitoring Budidaya Maggot Berbasis Aplikasi Android - Sianipar, Virgie Aubrey Hemas; Aini, Syifa Nurul; Pranoto, Dwitio Ahmad; Nurjihan, Shita Fitria; Supriyanto, Toto (Politeknik Negeri Jakarta, 2025)
Maggot is the larval phase of the life cycle of the Black Soldier Fly (BSF). The existence of maggot can be utilized as a solution to decompose organic waste as well as being used as an alternative feed for livestock. Good maggot results can be obtained by monitoring and controlling the cultivation process regularly. Monitoring and control need to be done to ensure the temperature and humidity of the cultivation site are in accordance with the needs of maggot. humidity in the cultivation site according to the needs of maggot, maggot maggots are protected from the threat of rat pests, food is given according to the schedule, and drying maggots that are ready for harvest. Maggot monitoring is carried out by utilizing an Internet of Things-based maggot cultivation monitoring system. The system design process consists of tool design and Android application design. The tool design uses a NodeMCU ESP32 microcontroller to operate the DC motor module and servo motor as a driver, a DHT-22 sensor to measure temperature and humidity, a PIR sensor to detect rat pests, an HC-SR04 sensor to measure maggot food levels, a fan to lower temperature and humidity, a buzzer as an alarm, OLED as a display to monitor temperature values, and RTC as a time recording module. The maggot monitoring and control system was successfully operated using an Android application to display temperature and humidity conditions, provide automatic feeding, repel rats and dry maggots.